Reducing prejudice through biased group contact? - Dambrauskas, Karolis (Socialinė teorija, empirija, politika ir praktika, 2019)
[full article and abstract in English]Using the methods of critical discourse analysis, this article analyzes the TV program Mission: Vilnija as an example designed to fight stereotypes about Lithuanian national minorities. The article shows how instead of improving inter-group relations, the program helps to ensure the status quo of unequal intergroup relations between the Lithuanian majority and the country’s national minorities. The case analysis supports the argument that if the idea of parasocial contact and prejudice reduction is built upon non-reflected, biased premises, it will not eliminate these forms of prejudice but will only preserve and/or reinforce them.
Keywords: contact theory; parasocial contact; prejudice; national minority